The role of MRI after neochemoradiotherapy in predicting pathological tumor regression grade and clinical outcome in patients with locally advanced rectal adenocarcinoma - Niu, Shaoqing; Chen, Yan; Peng, Fang; Wen, Jie; Xiong, Jianqi; Yang, Zhuangzhuang; Peng, Jianjun; Bao, Yong; Ding, Li (Frontiers in Oncology, 2023)
Objective: To evaluate the predictive value of tumor regression grade assessed by MRI (mr-TRG) after neoadjuvant chemoradiotherapy (neo-CRT) for postoperative pathological TRG (pTRG) and prognosis in patients with locally advanced rectal adenocarcinoma (LARC). Materials and Methods: This was a retrospective study from a single center experience. The patients who were diagnosed with LARC and received neo-CRT in our department between January 2016 and July 2021 were enrolled. The agreement between mrTRG and pTRG was assessed with the weighted κ test. Overall survival (OS), progress-free survival (PFS), local recurrence-free survival (LRFS), and distant metastasis-free survival (DMFS) were calculated by Kaplan-Meier analysis and log-rank test. Results: From January 2016 to July 2021, 121 LARC patients received neo-CRT in our department. Among them, 54 patients had complete clinical data, including MRI of pre- and post-neo-CRT, postoperative tumor samples, and follow-up. The median follow-up time was 34.6 months (range: 4.4-70.6 months). The estimated 3-year OS, PFS, LRFS and DMFS were 78.5%, 70.7%, 89.0%, and 75.2%, respectively. Out of 54 patients, 5 patients achieved mrTRG1 (9.3%), 37 achieved mrTRG2 (68.5%), 8 achieved mrTRG3 (14.8%), 4 achieved mrTRG4 (7.4%). Regarding pTRG, 12 patients achieved pTRG0 (22.2%), 10 achieved pTRG1 (18.5%), 26 achieved pTRG2 (48.1%), and 6 achieved pTRG3 (11.1%). The agreement between three-tier mrTRG (mrTRG1 vs. mrTRG2-3 vs. mrTRG4-5) and pTRG (pTRG0 vs. pTRG1-2 vs. pTRG3) was fair (weighted kappa=0.287). In a dichotomous classification，the agreement between mrTRG（mrTRG1 vs. mrTRG2-5）and pTRG（pTRG0 vs. pTRG1-3) also resulted in fair agreement (weighted kappa=0.391). The sensitivity, specificity, positive, and negative predictive values of favorable mrTRG (mrTRG 1-2) for pathological complete response (PCR) were 75.0%, 21.4%, 21.4%, and 75.0%, respectively. In univariate analysis, favorable mrTRG (mrTRG1-2) and downstaging N were significantly associated with better OS, while favorable mrTRG (mrTRG1-2), downstaging T, and downstaging N were significantly associated with superior PFS (p<0.05). In multivariate analysis, downstaging N was an independent prognostic factor for OS. Meanwhile, downstaging T and downstaging N remained independent prognostic factors for PFS. Conclusions: Although the consistency between mrTRG and pTRG is only fair, favorable mrTRG after neo-CRT may be used as a potential prognostic factor for LARC patients.